Proceso de reestructuración en los acuerdos y servicios en el proceso de selección de la empresa Ecuasanitas de octubre 2015 a marzo de 2016 - Almeida Reyes, Miguel Ángel (2016)
This project is aimed at improving the selection process applying tools and formats that contribute to knowledge skills of a candidate. It is important to consider that a candidate shows a portion of their characteristics and the others are hidden by what needs to be evaluated in depth. The selection process is crucial for the proper functioning of their departments and provide proper selection to the organizational culture of the entire company and issues such as adaptation time employee can define the quality of performance; I propose considering these points apply formats and tools has depth interviews, roll playing, formats work references, follow-up interviews that will support the process of adaptation of newly admitted personnel. An interview with the right tools is the best way to ensure that staff have the required and to conduct efficient screening the candidate will fit better in their work environment contributing positively to the organizational culture of the company is quality. In order to apply these tools it is necessary to socialize and train people involved in the improvement project as coordinators, heads of areas and peers. job security, increased performance level, a better working environment and a high level in the organizational culture of the company: to make an efficient selection process on issues such as an impact is generated. In the selection process improvements formats interview, job referrals, follow-up interviews will apply